Establishing the fluency gap between native and non-native-speech - Guz, Ewa (Research in Language, 2015)
Although various dimensions of speech fluency have so far generated a great deal of research interest, very few accounts have tackled the issue of the relationship between L1 and L2 fluency. Also, little empirical evidence has been provided to support the claim that language users are more fluent in their mother tongue than in a foreign/second language. This study examines the fluency gap between L1 and L2 fluency using a battery of objectively quantifiable temporal measures of speed and breakdown fluency. It also attempts to identify those temporal fluency variables which are affected by the individual way of speaking rather than the degree of automatisation of speech processing and which underlie oral performance both in L1 and L2. The analysis draws on transcriptions of elicited speech samples in L1 (Polish) and L2 (English).